cter\ combined mechanismA study on the Method of Condition Monitoring and Identifying for Gearboxes - 张西宁; 沈玉娣; 屈梁生 (Jixie chuandong)
Based on analysis of the consistency testing degree, this papel takes some efforts on the optimization to gear monitoring index set. By analysing the principal components of optimum monitoring index set, the paper makes it possible for identifying and monitoring gear operating condition, especially for detecting the occurrence of cracks on gears.